Distance Education and Remote Literacy Instruction: Experiences and Opinions of First-Grade Teachers During the Covid-19 Pandemic - Selda ÖZER; Mehmet Raci DEMİR (Hayef: Journal of Education)
First-grade students, their parents, and teachers met distance education (DE) and remote literacy instruction (RLI) as a result of the quarantine measures and rigorous regulations implemented to stop the spread of COVID-19. The aim of this study was to investigate first-grade teachers’ experiences and opinions on RLI in DE during the COVID-19 pandemic. Qualitative research paradigm and case study design were used to gather the data. Focus group interviews using a semi-structured interview form were carried out as a data collection method. The study group included 15 first-grade teachers working in public primary schools in Istanbul. Data were collected online, and content analysis was applied. The findings revealed that the teachers perceived DE as a crisis because they were more fatigued mentally. They could not communicate with their parents properly. They could not teach values. They could not manage the classroom. DE was also an opportunity because the teachers were less fatigued physically. They could develop professionally. While teaching online, teachers used various materials. They could apply different activities and instructional methods. They achieved student-student interaction as well as student-teacher interaction. Teachers could assess both reading comprehension and writing not only during the course but also after the course. They had some expectations and plans about school life after DE although they predicted to have some problems. They thought they could teach literacy online if they had to. The results highlighted the need for a sense of belonging, collaboration, and positive relationship among teachers, students and parents in RLI.